Checklist of insect pests and natural enemies associated with groundnut (Arachis hypogaea L.) ecosystem in Anaimalai tract of Tamil Nadu: CHECKLIST OF INSECT PESTS AND NATURAL ENEMIES ASSOCIATED WITH GROUNDNUT - T SRINIVASAN; R ARUL PRAKASH (Journal of Oilseeds Research, 2014)
Fixed and roving surveys were conducted at Coconut Research Station, Aliyarnagar and Anaimalai tract of Coimbatore district, Tamil Nadu to study the insect pests and natural enemy complex of groundnut ecosystem. Results of the study revealed the occurrence of 32 species of insect pests and 13 species of natural enemies. Among the insect pests, only five viz., Helicoverpa armigera, Spodoptera litura, Scirtothrips dorsalis, Empoasca kerri and Aphis craccivora were considered as major pests. Nine insect pests were considered as minor, while 18 were noticed as spot occurrence. The leafminer, Liriomyza trifolii population was noticed only during kharif season. Among the 13 species of natural enemies, coccinellid beetles viz., Coccinella transversalis and Cheilomenes sexmaculatus were dominant.